Delivery of the Brainshuttle™ amyloid-beta antibody fusion trontinemab to non-human primate brain and projected efficacious dose regimens in humans - Hans Peter Grimm; Vanessa Schumacher; Martin Schäfer; Sabine Imhof-Jung; Per-Ola Freskgård; Kevin Brady; Carsten Hofmann; Petra Rüger; Tilman Schlothauer; Ulrich Göpfert; Maximilian Hartl; Sylvia Rottach; et al. (Taylor & Francis Group, 2023)
ABSTRACTThere are few treatments that slow neurodegeneration in Alzheimer's disease (AD), and while therapeutic antibodies are being investigated in clinical trials for AD treatment, their access to the central nervous system is restricted by the blood-brain barrier. This study investigates a bispecific modular fusion protein composed of gantenerumab, a fully human monoclonal anti- amyloid-beta (Aβ) antibody under investigation for AD treatment, with a human transferrin receptor 1-directed Brainshuttle™ module (trontinemab; RG6102, INN trontinemab). In vitro, trontinemab showed a similar binding affinity to fibrillar Aβ40 and Aβ plaques in human AD brain sections to gantenerumab. A single intravenous administration of trontinemab (10 mg/kg) or gantenerumab (20 mg/kg) to non-human primates (NHPs, Macaca fascicularis), was well tolerated in both groups. Immunohistochemistry indicated increased trontinemab uptake into the brain endothelial cell layer and parenchyma, and more homogeneous distribution, compared with gantenerumab. Brain and plasma pharmacokinetic (PK) parameters for trontinemab were estimated by nonlinear mixed-effects modeling with correction for tissue residual blood, indicating a 4-18-fold increase in brain exposure. A previously developed clinical PK/pharmacodynamic model of gantenerumab was adapted to include a brain compartment as a driver of plaque removal and linked to the allometrically scaled above model from NHP. The new brain exposure-based model was used to predict trontinemab dosing regimens for effective amyloid reduction. Simulations from these models were used to inform dosing of trontinemab in the first-in-human clinical trial.